Parallel Patient Treatment Time Prediction Using Effective Queuing Recommendation System: Improving Patient Experience and Efficiency in Hospital Operations (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In hospital it is most challenges to reduce patient overcrowding and long time patient wait. Because of annoying waits for long periods ,it may increase frustration by patients .It will also be convenient for patients by this project to understand how much time they have to wait in queue, through a mobile application that updates in real time. It is also become possible to recognize the disease by selecting symptoms which display by using iterative and KNN algorithm. This project is also useful to display information of ambulance by area wise.